D’une industrie… l’autre ? - Sandrine Musso; Vinh-Kim Nguyen (Genre, Sexualité et Société)
Starting from a contextualization of Cindy Patton’s text, the authors invite consideration of the timeliness of these questions in light of contemporary issues related to the production of identities and communities that helps us see of the establishment of the « targets » of the prevention and treatment of HIV, as well as the effects of the depoliticization secured by the medicalization of the fight against the epidemic.